Skin layer-specific spatiotemporal assessment of micrometabolism during wound angiogenesis - Weiye Li; Yu-Hang Liu; Fumimasa Kubo; Sabine Werner; Daniel Razansky (Communications Biology)
Abstract Proper oxygen delivery through the microvasculature to injury site is essential to ensure the metabolic cascade during wound healing. Adaptation of vascular structure and oxygenation is key to unravel the regulation of blood perfusion, oxygen distribution and new tissue formation. Yet, visualizing micrometabolic responses at large scale in unperturbed living tissue remains challenging. We studied full-thickness excisional wounds in the mouse dorsal skin in vivo using ultrasound-aided spectroscopic large-scale optoacoustic microscopy. Skin layer-specific vascularization is visualized at capillary resolution over centimeter-scale field-of-view in a non-invasive, label-free manner. Different vascular parameters, including oxygenation, diameter and its irregularity, tortuosity and angular alignment, show distinct spatial and temporal variations. Elevated oxygenation is manifested close to the wound at day 4 with the trend accompanied by reduction in diameter over time. Angular alignment increases over time, indicating a more directed blood supply towards the wound. Our observations indicate that wound angiogenesis initiates as capillary sprouting with enlarged newborn vessels and elevated oxygenation around the wound, with the vessels normalizing in size and oxygenation during remodeling. Our study provides insight into micrometabolic profiles surrounding the healing wound, setting the stage for preclinical studies on oxygen delivery mechanisms in pathological skin conditions and during pharmacological interventions.